Isolation and Characterization of Bacterial Carbonate Precipitation for Biogrouting - Suyanto, Eko; Sari, Miranti Nurindah; Ratnakomala, Shanti; Fahrurrozi, Fahrurrozi; Gusmawati, Niken F. (BRIN, 2021)
Biogrouting is a process that transforms soil or sand into calcarenite or sandstone by bacterial calcium carbonate precipitation . The mechanisms of this process are that the bacteria hydrolyze urea catalyzed by urease, and with the existence of dissolved Ca2+, a solid crystalline calcite or calcium carbonate (CaCO3) will be produced. The main advantage of biogrout is that soil or sand can be strengthened without interfering with the hydraulics of the treated soil or sand and without excavation or replacement. In this study, the isolation and identification of bacterial calcium carbonate precipitation , and characterization of urease produced by bacteria were conducted. In the isolation method, the enrichment method using urea as abacterial carbon source was carried out. The formation of crystalline calcite was observed by a light microscope. The urease enzyme activity was determined by the 3, 5-Dinitrosalicylic acid (DNS) method. The molecular identification of isolates was analyzed by the determination of 16S rRNA gene sequencing. As a result, 19 calcium carbonate precipitation have been isolated from soils, sands, water, and rocks collected from several areas in Indonesia. They showed calcite formation in a medium with urea. Molecular identification of isolates with high urease enzyme activity revealed that the isolates belong to the group Bacilli. The highest enzyme activity produced by ID10-U004 is 374.94 U/mL. The preliminary biogrouting experiment was also conducted using isolated strain, and the reaction was able to make the sand solid and stiff.